Reconstruction of the left subclavian artery in arch repair: An end‐to‐side anastomosis technique. Issue 7 (19th April 2022) - Fujimori, Tomonari; Okamura, Homare; Kitada, Yuichiro; Wada, Yohnosuke; Adachi, Hideo
Abstract: Background: The left subclavian artery (LSCA) is deeply located and difficult to visualize in some cases of total arch replacement. Aims: We report an end‐to‐side anastomosis technique that enables safer and easier anatomical reconstruction of the LSCA. Materials and methods: Under Hypothermic circulatory arrest, the origin of the LSCA was ligated and pulled caudally. With clamping the distal LSCA, a graft was anastomosed to the anterior wall of the LSCA and antegrade cerebral perfusion to the LSCA was ensured through the anastomosed graft. Thereafter, distal anastomosis was performed proximal to the LSCA. Results: The postoperative course was uneventful. Discussion: Our reconstruction technique provides excellent exposure of the LSCA by pulling the origin of the LSCA caudally. Hemostasis after reconstruction is feasible, as the anastomosis in the anterior wall of the LSCA is easily visualized. Conclusion: The end‐to‐side anastomosis technique for LSCA reconstruction is a simple alternative in arch repair.